A Novel Sex-Dependent Target for the Treatment of Postoperative Pain: The NLRP3 Inflammasome - Cowie, Ashley M.; Dittel, Bonnie N.; Stucky, Cheryl L. (Frontiers in Neurology, 2019)
In recent years the innate immune system has been shown to be crucial for the pathogenesis of postoperative pain. The mediators released by innate immune cells drive the sensitization of sensory neurons following injury by directly acting on peripheral nerve terminals at the injury site. The predominate sensitization signaling pathway involves the proinflammatory cytokine interleukin-1β (IL-1β). IL-1β is known to cause pain by directly acting on sensory neurons. Evidence demonstrates that blockade of IL-1β signaling decreases postoperative pain, however complete blockade of IL-1β signaling increases the risk of infection and decreases effective wound healing. IL-1β requires activation by an inflammasome; inflammasomes are cytosolic receptors of the innate immune system. NOD-like receptor protein 3 (NLRP3) is the predominant inflammasome activated by endogenous molecules that are released by tissue injury such as that which occurs during neuropathic and inflammatory pain disorders. Given that selective inhibition of NLRP3 alleviates postoperative mechanical pain, its selective targeting may be a novel and effective strategy for the treatment of pain that would avoid complications of global IL-1β inhibition. Moreover, NLRP3 is activated in pain in a sex-dependent and cell type dependent manner. Sex differences in the innate immune system have been shown to drive pain and sensitization through different mechanisms in inflammatory and neuropathic pain disorders, indicating that it is imperative that both sexes are studied when researchers investigate and identify new targets for pain therapeutics. This review will highlight the roles of the innate immune response, the NLRP3 inflammasome, and sex differences in neuropathic and inflammatory pain.